Management of Cataract in Avicenna’s Canon of Medicine - Esmaeil Shabaninezhad; Samaneh Soleymani; Mohammad Reza Khalili; Alireza Mehdizadeh; Arman Zargaran (Journal of Research on History of Medicine, 2020)
Cataract is mentioned as one of the most important blindness factors in the world. Management and treatment methods of cataract dates back to antiquity. Avicenna is one of prominent Persian scientists that played an important role in the development of ophthalmology in ancient Persia. In this review, Avicenna’s points of view about cataract is discussed in the Canon of medicine and compared with the current medicine. Cataract or “Nozol-al-maâ” is an obstructive disease due to the accumulation of a dense liquid layer between the lens and cornea. Avicenna categorized cataracts based on their density, size and color. To treat and manage cataract, he took three approaches: changing life style and nutrition in the first step; using simple and complex medicines in the next step; and performing surgery in the last stage. Nowadays, in vivo and in vitro studies have proven the effects of some food, nutraceuticals and medicinal plants in preventing cataractogenesis progression. As surgery is the only remedy of cataract today and postoperative problems may occur, finding new non-surgical procedures can be noteworthy.